Spatiotemporal Characteristics and Trend of Puting Beliung Across the Indonesian Archipelago - Kiki, Kiki; Koesmaryono, Yonny; Hidayat, Rahmat; Perdinan, Perdinan; Permana, Donaldi Sukma (Indonesian Journal of Geography, 2025)
Puting beliung (PB), or small-scale tornado, is a significant and under-researched extreme weather phenomenon in Indonesia, often causing severe damage to infrastructure and posing risks to public safety despite their brief localized nature. Therefore, this research aimed to examine spatial and temporal patterns and trends of PB events across Indonesia from 2011 to 2024, applying statistical analysis, geospatial mapping, and the Mann-Kendall trend test to a database of 2,434 PB events. The results showed that PB events primarily cluster in western and central regions, specifically on Java Island, and the highest frequencies were observed in East Java, West Java, and Central Java. These events typically occur in low-lying zones (0–500 meters above sea level), affecting agricultural and residential land in flat terrain. Temporally, most PB arises in the afternoon (1:00–3:00 pm local time), with peak frequencies in January, March, and November, coinciding with Indonesian monsoonal and transitional seasons. A trend analysis shows a statistically significant nationwide yearly increase of approximately 12 PB events, with 8 provinces exhibiting notable upward patterns. When compared to other PB-prone nations, Indonesia records a higher annual PB frequency than Japan, Australia, and Bangladesh, but remains well below the United States. The novelty of this research lies in its long-term, nationwide dataset and thorough spatiotemporal assessment, providing the first comprehensive examination of PB trends at national and provincial scales in Indonesia. These results provide crucial insights for disaster risk mapping, mitigation strategies, and early warning systems.